The Influence of Electronic Word of Mouth, Trust and Product Quality On Purchase Decision of Fashion Product Through Online Shop: (Case Study : UMKM House of Sabrina In Surabaya) - Mukayati Mukayati (Journal of World Conference (JWC), 2019)
The purpose of this research to analyze the effect of electronic word of mouth, trust and product quality on purchasing decisions fashion products towards online shop at the House of Sabrina. This study design using quantitative methods the hypotheses by using SPSS version 20.0 with multiple linear regression analysis. The population this study were consumers of House of Sabrina. The sampling technique used was random sampling with the total 131 respondents who had purchased products by online. The results of this study show that electronic word of mouth variables, trust and product quality have an effect on simultaneously and significantly on purchasing decisions. Partially electronic word of mouth variables, trust and product quality have a significant effect on purchasing decisions. The Determination Coefficient value is 57.7% while the rest is influenced by other variables.